Plant-wide systems microbiology for the wastewater industry. Issue 10 (9th July 2021) - Cerruti, Marta; Guo, Bing; Delatolla, Robert; de Jonge, Nadieh; Hommes - de Vos van Steenwijk, Aleida; Kadota, Paul; Lawson, Christopher E.; Mao, Ted; Oosterkamp, Margreet J.; Sabba, Fabrizio; Stokholm-Bjerregaard, Mikkel; Watson, Ian; et al.
Abstract : Infiltrating systems microbiology concepts in the water industry requires the development of a language of love and shared endpoints in analytical bioscience and process engineering at the (waste)water line. Abstract : The wastewater treatment sector embraces mixed-culture biotechnologies for sanitation, environmental protection, and resource recovery. Bioprocess design, monitoring and control thrive on microbial processes selected in complex microbial communities. Microbial ecology and systems microbiology help access microbiomes and characterize microorganisms, metabolisms and interactions at increased resolution and throughput. Big datasets are generated from the sequencing of informational molecules extracted from biomasses sampled across process schemes. However, they mostly remain on science benches and computing clusters, without reaching the industry in a clear engineering objective function. A bilateral bridge should actionize this information. As systems microbiologists, we miss that engineering designs and operations rely on stoichiometry and kinetics. The added-value provided by microbial ecology and systems microbiology to improve capital (CAPEX) and operating expenditures (OPEX) needs to be addressed. As engineers, we miss that microbiology can be provide powerful microbial information on top of physical–chemical measurements for quantitative process design ( e.g., nutrient removal systems) with detailed scientific description of phenomena inside microbiomes. In this perspective article, we allied academia and industry to address the state of shared knowledge, successes and failures, and to establish joint investigation platforms. Our roadmap involves three milestones to (i) elaborate an essential list of microbiological information needed to implement methods at the process line; (ii) characterize microbiomes from microorganisms to metabolisms, and shape conceptual ecosystem models as primer for process ecology understanding; (iii) bridge engineering and mathematical models with an analytical toolbox for fast- vs. high-throughput analyses to discover new microbial processes and engineer assemblies. We praise for a harmonized "language of love" (incorporating common vocabulary, units, protocols) across the water and environmental biotechnology sector to team up mindsets for a sewer- and plant-wide integration of systems microbiology and engineering.